Immunoadolescence: Neuroimmune development and adolescent behavior. (November 2016) - Brenhouse, Heather C.; Schwarz, Jaclyn M.
Highlights: Maturation of the immune system continues through adolescence. Neuro-immune signaling controls neural development. We review evidence that adolescence is a unique stage of immune development. Neuro-immune development contributes to adolescent vulnerability to mental illness. We propose a need for understanding adolescence a period of neuro-immune signaling. Abstract: The brain is increasingly appreciated to be a constantly rewired organ that yields age-specific behaviors and responses to the environment. Adolescence in particular is a unique period characterized by continued brain maturation, superimposed with transient needs of the organism to traverse a leap from parental dependence to independence. Here we describe how these needs require immune maturation, as well as brain maturation. Our immune system, which protects us from pathogens and regulates inflammation, is in constant communication with our nervous system. Together, neuro-immune signaling regulates our behavioral responses to the environment, making this interaction a likely substrate for adolescent development. We review here the identified as well as understudied components of neuro-immune interactions during adolescence. Synaptic pruning, neurite outgrowth, and neurotransmitter release during adolescence all regulate—and are regulated by—immune signals, which occur via blood-brain barrier dynamics and glial activity. We discuss these processes, as well as how immune signaling during this transitional period of development confers differential effects on behavior and vulnerability to mental illness.